Lipid production from fed-batch fermentation of crude glycerol directed by the kinetic study of batch fermentations. (1st December 2017) - Chen, Jiaxin; Zhang, Xiaolei; Yan, Song; Tyagi, Rajeshwar Dayal; Drogui, Patrick
Highlights: Crude glycerol was converted to biodiesel by biotechnology. Kinetic study was performed to direct fermentation. Fed-batch fermentation was conducted according to the results of batch one. Abstract: Oleaginous yeast Trichosporon oleaginosus was cultivated in crude glycerol as substrate for lipid production in a 15 L fermenter. The impact of weight carbon to nitrogen ratio (C/N) including 20, 30, 45 and 60 on lipid production from the strain was investigated in batch fermentations. The highest biomass and lipid concentration of 24.80 g/L and 12.14 g/L, respectively was observed during the fermentation at C/N ratio of 45. C/N ratio of 30 showed a comparable concentration of biomass (23.70 g/L) and lipid (11.26 g/L). Based on the kinetic study of the batch fermentations, fed-batch fermentation was designed and conducted. In the fed-batch fermentation, the maximum concentration of biomass and lipid was 43.82 g/L and 21.87 g/L, respectively at C/N ratio of 45.